Hubungan aktivitas fisik lansia elderly (60-74 tahun) dengan fungsi kognitif - Zakirullah Zakirullah; Zuliani Zuliani; Alfian Helmi (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Physical activity is any body movement that generates energy to do it. Elderly due to degenerative, there will be a decrease in cognitive function, namely mental processes in obtaining knowledge or abilities and intelligence, including ways of thinking, and memory. This decrease in cognitive function is a normal condition experienced by the elderly with increasing age. This lack in cognitive function can be inhibited by taking preventive measures by increasing physical activity.Objective: To determine the relationship between physical activity of older adults (60-74 years) and cognitive function.Method: The design of this research is descriptive-analytic with a cross-sectional approach. The sampling technique using cluster sampling is done by interview and questionnaire. The number of samples is 60 elderly respondents.Results: This study was dominated by male elderly aged 60-74 years, unemployed, who had elementary and junior high school education, and had chronic diseases. The results showed that there was a relationship between physical activity in the elderly (60-74 years old) with cognitive function (p = 0.01; = 0.05).Conclusion: It is expected to be a reference for one of the efforts to prevent cognitive decrease by increasing physical activity in the form of physical exercise, then a study can be conducted on the intensity, duration, frequency, and type of physical exercise that is best for improving the cognitive function of the elderly.